Psychological Aspects in Terms of Physical, Mental and Sociological Factors During Worldwide Corona Crisis - Akanksha Mandal (Institute of Medico-legal Publications Pvt Ltd, 2021)
Severe acute respiratory syndrome is a viral disease affecting the respiratory system , cause by coronavirus.The epidemic lasted for 2 years till May 2004 when WHO declared China to be free of new cases but statedthat “ biosafety concerns remain” In 2019, SARS-CoV-2 was discovered which later in the present havecaused the COVID-19 pandemic. The first case was identified in Wuhan, china and which later on turnedto worldwide pandemic. The WHO had declared the outbreak a public health emergency of internationalconcern on 30 January 2020 and a PANDEMIC on 11th march 2020.Considering the present scenario , there are certain articles over the internet and journals which have givenus a bunch of ideas over different aspects of life. Some of the long list of concepts are physical health, mentalhealth, local market uprising, and concept of work from home .Based on gathered information via discussions, surveys and personal interactions with thousands ofindividuals, differing in age, by gender and by occupations, these hereby key points and key lessons havecome to light and here is a brief description in terms of physical health , mental health, effect of lockdownon local market and effect of work from home on people.